Penggunaan Media Loose Parts untuk Meningkatkan Kreativitas Anak Usia 5-6 Tahun - Khairunnisa Febrianti; Arum Tri Istikhomah; Aprilya Nur Fitriani; Ellysa Aditya Suryawati; Ismatul Khasanah (UNIB Press, 2026)
This study aimed to improve the creativity of children aged 5-6 years through the use of loose parts media at TK Pertiwi Lau Dawe Kudus. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consisted of planning, action, observation, and reflection stages conducted in two cycles. The participants were 12 children from Group B. Data were collected through observation, interviews, and documentation. The research instrument used an observation sheet covering creativity indicators such as originality, elaboration, curiosity, imagination, risk-taking, exploration, and initiative. The findings revealed that the use of loose parts media significantly improved children's creativity. In the pre-cycle stage, no children reached the “Very Well Developed” category (0%). After the implementation of Cycle I, the percentage increased to 25%, and further improved to 83% in Cycle II. The learning process became more interactive, enjoyable, and child-centered, allowing children to freely explore, imagine, and create based on their own ideas. The study concludes that loose parts media is effective in enhancing early childhood creativity and can be used as an innovative learning medium in early childhood education settings.